The end of the story - Davis, Lydia 1947- (Farrar, Straus and Giroux, 1995)
A woman attempts to recover from a failed love affair by writing a novel on the subject and finds it a difficult task. The hardest part is the chronology, who did what to whom first. She describes the affair in narrative form, without dialogue, from its happy beginnings--he was good looking, a poet, 12 years her junior--to the sordid finale when she turned to stalking him. By the author of Break It Down.